The Necessary Condition For Fixed Points In The Inverse Limits Spaces - Ali H. Ali; Faruq A. Mena (Tikrit Journal of Pure Science)
A point  in the inverse limit space is said to be a cut point of this space when excluded from it, when the number of the components of that space increases. Therefore, this study aims at finding the necessary condition for fixed points in the inverse limit space to be cut points. Then, for applying the main theorem with some conditions, a sequence of upper semi continuous can be employed as a bonding function to get a union of continua as a generalized inverse limit space if there is a generalized inverse limit for each of them separately.